2018
DOI: 10.1111/jdv.15157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors and comorbidity of dry skin in the general population

Abstract: Dry skin is a frequent condition in the adult general population and needs special attention. Known risk factors may facilitate identifying patients at risk for deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 16 publications
2
74
2
11
Order By: Relevance
“…The term ‘comorbidity’ was used as published previously to characterize any association of two or more disease entities regardless of causality. For this, distinct skin diseases occurring in a single individual are commonly named ‘comorbid dermatological conditions’ . Although there may be pathogenetic associations between a number of inflammatory skin conditions, such as psoriasis and seborrhoeic dermatitis, we kept these conditions as separate entities and used the term ‘comorbidity’.…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘comorbidity’ was used as published previously to characterize any association of two or more disease entities regardless of causality. For this, distinct skin diseases occurring in a single individual are commonly named ‘comorbid dermatological conditions’ . Although there may be pathogenetic associations between a number of inflammatory skin conditions, such as psoriasis and seborrhoeic dermatitis, we kept these conditions as separate entities and used the term ‘comorbidity’.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational screening exams in Germany (n = 48,380) have revealed that approximately every third employee (29.4 %) between the age of 16 and 70 years is affected by xerosis cutis. There is no gender predilection . The prevalence increases with increasing age (55.6 % at a mean age of 75.1 years) .…”
Section: Background and Rationalementioning
confidence: 94%
“…Augustin et al. (2018) have shown that xerosis cutis is associated with an increased risk of developing axillary dermatitis, atopic dermatitis, exsiccation eczematoid, psoriasis, plantar warts and seborrheic dermatitis . Elderly, care‐dependent individuals with dry skin show a diminished defense against external pathogens and an increased risk of developing decubital ulcers .…”
Section: Background and Rationalementioning
confidence: 99%
“…The effects caused by the vehicle seem to be more pronounced than the result obtained with a urea-ceramide-lactate-based formulation, which was previously proposed for the treatment of dry skin [32]. Since a stable epidermal barrier function is related to optimal skin hydration, especially elderly persons could benefit from topicals containing Lactococcus lysate, as they are particularly prone to suffering from xerosis [33-35]. …”
Section: Discussionmentioning
confidence: 85%